Analyzing the Mediating Effects of Social Capital and Sense of Community Between International Student’s College Sports Team Identification and Acculturation - Kibaek Kim; Sarah Stokowski; Alison Fridley; Jinwook Han (Journal of Intercollegiate Sport, 2023)
Previous studies focused on the role of leisure activities, such as physical activity participation, to analyze how international students can receive social support from their communities to better acculturate in the U.S. This study focused on the role of college sports in providing social support and its effect on international student’s acculturation. Four hundred eighty-seven international students enrolled in 25 Power-5 affiliated colleges participated in this study to analyze the acculturation path model suggested by the primary researcher. The initial path model did not show a statistically significant model fit, which led to modifying the model once following the available theory in academia. As a result, the proposed model resulted in a good model fit (RMSEA = .03, SRMR = .01, CFI = 1.00, TLI = .98). Discussions on utilizing spectator sports to promote international students’ acculturation, suggestions for future study options, and limitations of the study were provided.